Prognostic Value of TRPM7 Expression and Factor XIIIa-Expressing Tumor-Associated Macrophages in Gastric Cancer - Calik, Muhammet; Calik, Ilknur; Artas, Gokhan; Ozercan, Ibrahim Hanifi (Wiley, 2021)
Purpose. TRPM7 is known to play a key role in tumor progression by regulating cellular proliferation, migration, and invasion in various cancer cell lines. However, there are no comprehensive clinical studies about the effect of TRPM7 expression on gastric cancer (GC) prognosis. In this study, it was aimed at investigating the effect of TRPM7 expression on prognosis in GC patients. Additionally, for the first time, it was investigated whether the density of Factor XIIIa-expressing tumor-associated macrophages (TAMs) in GC has an effect on the biological behaviour of the tumor. Methods. TRPM7 expression and Factor XIIIa-expressing TAM density were immunohistochemically evaluated in paraffin-embedded tumor tissues of 204 GC patients undergoing surgery at a single institution. Results. Tumor size was clearly higher in cases with high TRPM7 expression than those with low expression (p<0.001, Mann-Whitney U). TRPM7 overexpression was closely related to high depth of tumor invasion (p<0.001, ANOVA), increased lymph node metastasis (p<0.001, ANOVA), and high distant metastasis rate (p<0.001, Mann-Whitney U). These findings exposed that high TRPM7 expression is effective in the progression and aggressiveness of GC. In addition, while high CD8(+) TIL density affects the prognosis positively, it was determined that high Factor XIIIa(+) TAM density negatively affects the prognosis of patients with GC. Furthermore, multivariate analyses revealed TRPM7 overexpression was independently related with short overall (HR 9.64, 95% CI 5.74-16.19, p<0.001) and disease-free survival (HR 5.67, 95% CI 3.61-8.92, p<0.001) in GC patients. Conclusions. Our data suggest that high TRPM7 expression is closely related to progressive tumor behaviour in GC and independently negatively affects survival in patients. In addition, it was determined that a high density of Factor XIIIa(+) TAMs negatively affects the prognosis of patients with GC.
Keywords: Epithelial-Mesenchymal Transition; Ion Channels; Invasion; Proliferation; Polarization; Metastasis; Carcinoma; Migration; Hallmarks; Induce